Handheld echocardiographic screening for rheumatic heart disease by non-experts. Issue 1 (5th October 2015) - Ploutz, Michelle; Lu, Jimmy C; Scheel, Janet; Webb, Catherine; Ensing, Greg J; Aliku, Twalib; Lwabi, Peter; Sable, Craig; Beaton, Andrea
Abstract : Objectives: Handheld echocardiography (HAND) has good sensitivity and specificity for rheumatic heart disease (RHD) when performed by cardiologists. However, physician shortages in RHD-endemic areas demand less-skilled users to make RHD screening practical. We examine nurse performance and interpretation of HAND using a simplified approach for RHD screening. Methods: Two nurses received training on HAND and a simplified screening approach. Consented students at two schools in Uganda were eligible for participation. A simplified approach (HAND performed and interpreted by a non-expert) was compared with the reference standard (standard portable echocardiography, performed and interpreted by experts according to the 2012 World Heart Federation guidelines). Reasons for false-positive and false-negative HAND studies were identified. Results: A total of 1002 children were consented, with 956 (11.1 years, 41.8% male) having complete data for review. Diagnoses included: 913 (95.5%) children were classified normal, 32 (3.3%) borderline RHD and 11 (1.2%) definite RHD. The simplified approach had a sensitivity of 74.4% (58.8% to 86.5%) and a specificity of 78.8% (76.0% to 81.4%) for any RHD (borderline and definite). Sensitivity improved to 90.9% (58.7% to 98.5%) for definite RHD. Identification and measurement of erroneous colour jets was the most common reason for false-positive studies (n=164/194), while missed mitral regurgitation and shorter regurgitant jet lengths with HAND were the most common reasons for false-negative studies (n=10/11). Conclusions: Non-expert-led HAND screening programmes offer a potential solution to financial and workforce barriers that limit widespread RHD screening. Nurses trained on HAND using a simplified approach had reasonable sensitivity and specificity for RHD screening. Information on reasons for false-negative and false-positive screening studies should be used to inform future training protocols, which could lead to improved screening performance.